2015
DOI: 10.1002/jso.23887
|View full text |Cite
|
Sign up to set email alerts
|

Radical cystectomy in patients over 80 years old in Quebec: A population‐based study of outcomes

Abstract: A total of 275 patients over 80 years old had RC performed in 38 hospitals across Quebec. Among them, 33% had major post-operative complications with 16% having more than one complication. Mortality rates at 30, 60 and 90 days were 5.8%, 9.8% and 13% respectively. 44.3% of RCs were performed in seven academic hospitals with mortality rates of 2.5%, 6.5% and 9% respectively. Community hospitals had mortality of 8.5%, 12.4% and 16.3% respectively (P < 0.001). The cohort 5-year overall survival rate was 27%. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…The basis for the dichotomizing year of surgery was to compare our new cohort (2010‐2015) to the existing cohort on which we published previously (2000‐2009) . Coincidentally, when analyzing individual years, we observed a similar survival rate in patients undergoing RC between 2000 and 2008, and in patients undergoing surgery between 2010 and 2015 (data not shown).…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The basis for the dichotomizing year of surgery was to compare our new cohort (2010‐2015) to the existing cohort on which we published previously (2000‐2009) . Coincidentally, when analyzing individual years, we observed a similar survival rate in patients undergoing RC between 2000 and 2008, and in patients undergoing surgery between 2010 and 2015 (data not shown).…”
Section: Discussionmentioning
confidence: 56%
“…We have previously reported the clinical outcome after RC between 2000 and 2009, using data from Québec provincial registries. 3,5,[10][11][12][13][14][15][16] In these studies, we concluded among others that overall survival was improved in patients who had an RC performed by high-volume surgeons and in high-volume hospitals. 5 In the current manuscript, Readmission rates are shown as the number of patients readmitted within 30/60/90 days after initial discharge, divided by the total number of patients (%).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations